Teaching a great Yurchenko layout vault - Uzunov, V. (Gym Coach, 2011)
This article continues on from the discussion presented in "Qualitative description of the ideal Yurchenko layout vault technique" published in Vol 4, 2010 issue of the Gym Coach Journal. In the first part of our discussion and examination of the Yurchenko layout, it was concluded from available research and data that all good Yurchenko vaulting performances had three biomechanical characteristics in common: an appropriate CM pre-flight velocity, a high level of pre-flight angular momentum and contact the horse with a large body angle of attack. The purpose of this article is to use the insight from the previous discussion and practically apply it in the presentation of a methodological model for coaching of the Yurchenko layout vault. The training model presented uses a series of drills, progressions, and specific physical preparation exercises chosen for their specificity and development of the key biomechanically factors identified with successful Yurchenko layout performance.